Autoinducer-2-based quorum sensing of foodborne pathogenic bacteria under food related conditions - Yoon, Yohan, author; Sofos, John, advisor; Kendall, Patricia, advisor; Ellis, Robert P., committee member; Scanga, John, committee member (Colorado State University. Libraries, 2006)
The objective of these studies was to evaluate potential involvement of autoinducer (AI)-2-based quorum sensing (quorum sensing: cell density dependent cell-to-cell signaling) of foodborne pathogenic bacteria in food environments. Under the conditions of these studies, AI-2 activity of Salmonella and Escherichia coli O157:H7 was not associated with rate of bacterial growth. Production of AI-2 was increased in the presence of glucose (0.5%), and AI-2 activity of E. coli O157:H7 was not very high in beef purge containing high levels of natural flora. Salmonella and E. coli O157:H7 did not form more (P≥0.05) biofilm on food contact surfaces in the presence of AI-2 activity compared to absence of AI-2 activity, suggesting that AI-2-based quorum sensing may not be involved in biofilm formation by Salmonella and E. coli O157:H7 on food contact surfaces. AI-2-like activity increased (P<0.05) in fresh beef samples inoculated with E. coli O157:H7, containing lower levels of natural flora, and stored at higher temperature (25°C) and under aerobic conditions. Under heat (55°C) and acid stress (pH 3.0 or 3.5), surviving cell counts of Salmonella were not different (P≥0.05) in the presence and absence of AI-2 activity, indicating that AI-2-based quorum sensing of Salmonella may not be involved in heat and acid stress response. Surviving cell counts of E. coli O157:H7 were higher (P<0.05) in the presence than in the absence of AI-2 activity under both heat (52 or 55°C) and acid (pH 3.0) stress, indicating that AI-2-based quorum sensing of E. coli O157:H7 may be partially involved in mechanisms of heat and acid resistance. The results of these studies may be potentially helpful in developing novel approaches for improving food safety, while research on quorum sensing should be continued with the goal of finding targets for pathogen control in foods.
Keywords: microbiology